Pemberdayaan Masyarakat melalui Edukasi Hipertensi dan Pemantauan Tekanan Darah di Wilayah Kerja PKM Jalan Gedang Kota Bengkulu - Fernando, Frengki; Dameza, Afdilliyah Suci Sukma; Afriani, Novita; Sari, Rahayu Widia; Kartika, Kartika; Rossita, Taufianie (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Hypertension is one of the most common health problems found in the community and can lead to serious complications if not properly controlled. Low public knowledge regarding risk factors, symptoms, and prevention of hypertension can influence health behavior and compliance in monitoring blood pressure. This educational activity aimed to increase the knowledge of residents in RT 09 about hypertension and to identify their blood pressure status after measurements were taken. The study used a pre–post test design involving 21 participants. The results showed a significant improvement in knowledge, where before the education session, 52.4% of respondents were in the “fair” knowledge category and only 19% were in the “good” category. After the education, the percentage of respondents with “good” knowledge increased to 81%. In addition, blood pressure measurements indicated that 61.9% of residents were categorized as having hypertension, while 38.1% were not hypertensive. These findings suggest that health education is effective in improving community knowledge and that the prevalence of hypertension in the area is relatively high, indicating the need for continuous promotive and preventive efforts.